2013
DOI: 10.1039/c3an36840h
|View full text |Cite
|
Sign up to set email alerts
|

Simple pyridyl-salicylimine-based fluorescence “turn-on” sensors for distinct detections of Zn2+, Al3+ and OH− ions in mixed aqueous media

Abstract: Simple pyridyl-salicylimine derivatives (F1, F2 and F3) are reported for the first time as fluorescence "turn-on" sensors for distinct detections of Zn(2+), Al(3+) and OH(-) ions in mixed-aqueous media CH3CN/H2O with volume ratios of 6/4 and 3/7 (at pH = 7 and 25 °C) via internal charge transfer (ICT), chelation enhanced fluorescence (CHEF), and deprotonation mechanisms. F1 and F2 show diverse turn-on sensing applications to Zn(2+), Al(3+) and OH(-) ions, but F3 exhibited the fluorescence turn-on sensing to Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…[57] The detection limit is comparable to the reported (10 -6 mol·L -1 ). [58,59] These results demonstrated that HL is highly selective and sensitive for Al 3+ ion.…”
Section: Fluorescence Response To Metal Ionsmentioning
confidence: 65%
“…[57] The detection limit is comparable to the reported (10 -6 mol·L -1 ). [58,59] These results demonstrated that HL is highly selective and sensitive for Al 3+ ion.…”
Section: Fluorescence Response To Metal Ionsmentioning
confidence: 65%
“…S6). The observed fluorescent enhancement may be attributed to the formation of a rigid system after binding with Al 3+ , causing the chelation-enhanced fluorescence (CHEF) effect [28][29][30]. This unique selectivity of receptor 2 toward Al 3+ could be interpreted in terms of the smaller ionic radii and higher charge density of the Al 3+ ion.…”
Section: Fluorescence and Absorption Studies Of Receptor 2 Toward Varmentioning
confidence: 98%
“…7 Therefore, it is important topic to design and develop effective analytical methods or instruments for detection of aluminum ions in environmental and/or biological systems. Although many different and sophisticated analytical techniques including inductively coupled plasma emission (ICP-OES) or mass spectrome-try (ICP-MS), and atomic absorption spectrometry have been used extensively for the detection of aluminum ions, 8,9 most of these techniques have some disadvantages such as time consuming, qualified personal and high cost. 10 But among them, fluorescence spectroscopy is most popular analytical instrument for the detection of metal ions and it is preferred intensively by scientists in analytical applications owing to its easy operation, comparatively low cost, and high sensitivity, etc.…”
Section: Introductionmentioning
confidence: 99%